Epidemiology of childhood tuberculosis after ceasing universal Bacillus Calmette–Guérin vaccination - Sayori Kobayashi (Nature Portfolio, 2021)
Abstract Universal Bacillus Calmette–Guérin (BCG) vaccination is recommended in countries with high tuberculosis (TB) burden. Nevertheless, several countries have ceased universal BCG vaccination over the past 40 years, with scarce comparative epidemiological analyses regarding childhood TB after the policy change. We analysed data on childhood TB in countries that ceased universal BCG vaccination. Data sources included national/international databases, published papers, annual TB reports, and public health authority websites. Childhood TB notification rate increased in one of seven countries with available data. Pulmonary TB and TB lymphadenitis were the main causes of increasing childhood cases, while changes in severe forms of TB cases were minor. Maintaining high vaccine coverage for the target group was a common challenge after shifting selective vaccination. In some countries showing no increase in childhood TB after a BCG policy change, the majority of childhood TB cases were patients from abroad or those with overseas parents; these countries had changed immigration policies during the same period. Heterogeneity in childhood TB epidemiology was observed after ceasing universal BCG vaccination; several factors might obscure the influence of vaccination policy change. Lessons learned from these countries may aid in the development of better BCG vaccination strategies.